PENGUKURAN MUTU LAYANAN POSYANDU SEBAGAI UPAYA MENGURANGI KASUS BALITA TENGKES - Tasari, Tasari; Hersulastuti, Hersulastuti; Nugroho, Arif Julianto Sri; Suranto, Much; Wulandari, Aniek; Christanti, Paramita Lea (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
In particular, this study aimed to test the value of the gap and efforts to close the gap through the Servqual test. The population in this study were housewives who had children under five receiving Posyandu (Integrated Healthcare Center) services. Sampling used purposive sampling of 20 respondents in the Posyandu area of ​​Jogonalan Village, Klaten. Attributes in the service quality questionnaire included tangibles, reliability, responsiveness, assurance and empathy. Quantitative tests carried out included item reliability validity test, Servqual confirmation test. The test results show that the confirmation value has a positive value with the lowest positive value on the tangible dimension. Improvement efforts must continue to be made with the emphasis on improvement on the value that has the lowest positive dimension followed by the next positive value. The increasing quality of Posyandu KB (Family planning )services in Jogonalan Village leads to community satisfaction so that it can become a stronghold against cases of stunting infants under five years of age in urban areas.